Question 13 (OR 1 st question)

Prove that the function f:[0, ∞) → R given by f(x) = 9x 2 + 6x – 5 is not invertible. Modify the codomain of the function f to make it invertible, and hence find f –1 .

Slide34.JPG

Slide35.JPG
Slide36.JPG Slide37.JPG Slide38.JPG Slide39.JPG Slide40.JPG Slide41.JPG Slide42.JPG

  1. Class 12
  2. Sample Papers, Previous Year Papers and Other Questions
Ask Download

Transcript

Question 13 (OR 1st question) Prove that the function f:[0, ∞) → R given by f(x) = 9x2 + 6x – 5 is not invertible. Modify the codomain of the function f to make it invertible, and hence find f–1 . If f(x) is invertible f(x) is one-one f(x) is onto First, let us check if f(x) is onto Let f(x) = y y = 9x2 + 6x – 5 0 = 9x2 + 6x – 5 – y 9x2 + 6x – 5 – y = 0 9x2 + 6x – (5 + y) = 0 Comparing equation with ax2 + bx + c = 0 a = 9, b = 6 , c = – (5 + y) x = (−𝑏 ± √(𝑏^2 − 4𝑎𝑐))/2𝑎 Putting values x = (− 6 ± √(6^2 − 4(9) (−(5 + 𝑦)) ))/2(9) x = (− 6 ± √(36 + 36(5 + 𝑦)))/18 x = (− 6 ± √(36(1 + (5 + 𝑦)) ))/18 x = (− 6 ± √(36(6 + 𝑦) ))/18 x = (− 6 ± 6 √((6 + 𝑦)))/18 x = 6[− 1 ± √((6 + 𝑦) )]/18 x = (− 1 ± √((6 + 𝑦) ))/3 So, x = (− 1 − √((6 + 𝑦) ))/3 or (− 1 + √((6 + 𝑦) ))/3 As x ∈ [0, ∞) , i.e., x is a positive real number x cannot be equal to (−1 − √((6 + 𝑦) ))/3 Hence, x = (−1 + √((6 + 𝑦) ))/3 Since y ∈ R For y = –6 x = (−1 + √((6 − 6) ))/3 = (−1)/3 Since x = (−1)/3 ∉ [0, ∞) So, f is not invertible To make it invertible, x ≥ 0 (−1 + √((6 + 𝑦) ))/3 ≥ 0 –1 + √((6 + 𝑦) ) ≥ 0 √((6 + 𝑦) ) ≥ 0 + 1 √((6 + 𝑦) ) ≥ 1 6 + y ≥ 1 y ≥ 1 – 6 y ≥ –5 So, our domain should be [–5, ∞) Now, our function is f: [0,∞) → [–5, ∞) f(x) = 9x2 + 6x – 5 We need to first check if it is one-one and onto Checking one-one f (x1) = 9(x1)2 + 6x1 – 5 f (x2) = 9(x2)2 + 6x2 – 5 Putting f (x1) = f (x2) 9(x1)2 + 6x1 – 5 = 9(x2)2 + 6x2 – 5 9(x1)2 – 9(x2)2 + 6x1 – 6x2 = – 5 + 5 9(x1)2 – 9(x2)2 + 6x1 – 6x2 = 0 9[(x1)2 – (x2)2 ]+ 6[x1 – x2] = 0 9[(x1 – x2) (x1 + x2) ]+ 6[x1 – x2] = 0 3(x1 – x2) [3(x1 + x2) + 2] = 0 (x1 – x2) [3x1 + 3x2 + 2] = 0/3 (x1 – x2) [3x1 + 3x2 + 2] = 0 (x1 – x2) = 0 ⇒ x1 = x2 (3x1 + 3x2 + 2) = 0 ⇒ 3x1 = –3x2 – 2 Since x ∈ [0, ∞) i.e. x is always positive, Hence 3x1 = – 3x2 – 2 is not true Hence, if f (x1) = f (x2) , then x1 = x2 ∴ f is one-one Hence, if f (x1) = f (x2) , then x1 = x2 ∴ f is one-one Since the function is one-one and onto ∴ It is invertible Calculating inverse For finding inverse, we put f(x) = y and find x in terms of y We have done that while proving onto x = (−1 + √((6 + 𝑦) ))/3 Let g(y) = (−1 + √((6 + 𝑦) ))/3 where g: [–5,∞ ) → [0, ∞) So, inverse of f = f–1 = (−𝟏 + √((𝟔 + 𝒚) ))/𝟑

About the Author

Davneet Singh's photo - Teacher, Computer Engineer, Marketer
Davneet Singh
Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 8 years. He provides courses for Maths and Science at Teachoo. You can check his NCERT Solutions from Class 6 to 12.